Prothrombotic Risk Factors in Children with Acute Lymphoblastic Leukemia Treated with Delayed E. coli Asparaginase (COALL-92 and 97 Protocols) - Mauz-Körholz, Christine; Junker, Ralf; Göbel, Ulrich; Nowak-Göttl, Ulrike (Thrombosis and Haemostasis, 2000)
Hereditary prothrombotic risk factors have been shown to increase the risk of venous thrombosis in children treated with the combination of E. coli asparaginase and steroids. In the present study the role of prothrombotic risk factors in children with ALL treated according to the COALL study protocol was investigated in 108 consecutively recruited childhood patients. The prevalence rates of prothrombotic risk factors [factor V G1691A mutation, the prothrombin G20210A variant, the TT677 methylenetetrahydrofolate reductase genotype, deficiencies of protein C, protein S, antithrombin, elevated lipoprotein (a)] in this cohort were within the range reported for healthy Caucasians, and comparable to previously reported data for other leukemic patients. Venous thromboembolism occurred in 3 of the 108 children (induction n = 1; reinduction n = 2: 2.8%), and none of these children carried a prothrombotic risk factor. The results of the present study, suggest that the role of hereditary and acquired disturbances of coagulation in the development of thromboses might depend on the treatment regimen.
Keywords: Childhood ALL; prothrombotic risk factors; symptomatic thromboembolism